Cybersecurity readiness in Thailand: The empirical evidence of service sectors - Photipatphiboon, Porramin; Chokpiriyawat, Thanuset; Papamo, Kanokwan (Edelweiss Applied Science and Technology, 2025)
This study evaluates the cybersecurity maturity of Thailand's service sectors amid digital transformation. As advanced technologies become increasingly adopted in industries such as healthcare, education, tourism, and finance, these sectors encounter significant cybersecurity challenges due to the sensitivity of customer data and system interconnectivity. Utilizing the Technology, Organization, and Environment (TOE) framework, the study assesses cybersecurity readiness concerning technological, organizational, and environmental factors. Data were collected from 400 respondents through purposive sampling, and structural equation modeling (SEM) was employed for analysis. The study finds that technological, organizational, and environmental readiness significantly influence cybersecurity awareness. Among these, environmental readiness emerged as the most impactful, with external pressures like regulatory compliance and market competition shaping cybersecurity preparedness. Additionally, cybersecurity awareness strongly affects compliance behavior and the willingness to share cybersecurity knowledge within organizations. Cybersecurity awareness is crucial for improving compliance with security protocols and fostering a proactive cybersecurity culture. Strengthening awareness and preparedness across technological, organizational, and environmental levels is essential for effectively managing cybersecurity risks in service sectors undergoing digital transformation. The findings underscore the need for tailored cybersecurity policies and targeted training programs to build resilience against cyber threats, particularly in developing economies. The proposed framework and quantifiable index provide a practical tool for organizations to assess and improve cybersecurity readiness, ensuring better protection of sensitive data and regulatory compliance.